Se distraire la nuit à Dakar - François Singue Diouf; Meissa Birima Fall (EchoGéo)
At night, Dakar, the capital of Senegal, is a city that hosts recreational activities in both closed and open spaces. This trend, a reflection of growing urbanity, has socio-spatial consequences that are documented here by a state of the art and in situ observations through field surveys. The Almadies district in the commune of Ngor is particularly noteworthy within the city for the concentration of leisure spaces and actors that have turned it into a nightlife hub. We note the emergence of a nocturnal recreational centrality with leisure establishments and differentiated actors, diversified practices and uses testifying to the social and spatial recomposition of the city of Dakar at night.